2015
DOI: 10.3390/jcm4050884
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Atopic Dermatitis: Mimics, Overlaps, and Complications

Abstract: Atopic dermatitis (AD) is one of the most common skin diseases affecting infants and children. A smaller subset of adults has persistent or new-onset AD. AD is characterized by pruritus, erythema, induration, and scale, but these features are also typical of several other conditions that can mimic, coexist with, or complicate AD. These include inflammatory skin conditions, infections, infestations, malignancies, genetic disorders, immunodeficiency disorders, nutritional disorders, graft-versus-host disease, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 78 publications
3
87
0
6
Order By: Relevance
“…Concomitant psoriasis and atopic dermatitis is occasionally encountered, and many children with psoriasis have a psoriasiform dermatitis that is intermediate between psoriasis and dermatitis, often without the sharply delineated, very scaly lesions that are typical of psoriasis in adults. This condition is also referred to as overlap, eczematous psoriasis, or psoriasiform eczema …”
Section: Differential Diagnosismentioning
confidence: 99%
“…Concomitant psoriasis and atopic dermatitis is occasionally encountered, and many children with psoriasis have a psoriasiform dermatitis that is intermediate between psoriasis and dermatitis, often without the sharply delineated, very scaly lesions that are typical of psoriasis in adults. This condition is also referred to as overlap, eczematous psoriasis, or psoriasiform eczema …”
Section: Differential Diagnosismentioning
confidence: 99%
“…The association between the 2 conditions has been described as psoriasis-eczema overlap or eczematous psoriasis. Typically, people with psoriasis-eczema overlap have both flexural eczema and psoriatic lesions, and although no thick plaques are present, patients experience more intense itching than in isolated psoriasis [35] (Figure 15). …”
Section: Psoriasiform Dermatitismentioning
confidence: 99%
“…To the Editor, Some children present with a so-called overlap condition with clinical features of both psoriasis and atopic dermatitis (AD), previously described as 'psoriasis dermatitis' (PD). [1][2][3] Though its existence is not questioned in literature, only one study demonstrated clinical characteristics of children with coexisting psoriasis and AD, 2 and its course over time has not been described so far.…”
mentioning
confidence: 99%